Advancing the robustness of risk regulation for offshore drilling operations in China - Yang, Yuan (Frontiers in Marine Science, 2023)
Robust regulation has become a pursuit of risk governance of offshore drilling operations over recent decades. Yet, for all its discussion, the ideas of robust regulation have not been fully developed in China. This paper aims to explore how China can establish a robust regulatory regime on health, safety, and environment for offshore operations in comparison with regimes of the United Kingdom, Norway, and the United States. It begins with an identification of risks and values in offshore petroleum industry, highlighting that robust regulation is the primary means to manage such risks of offshore drilling operations. This is followed by an analysis of dimensions of regulatory robustness, and regulatory regimes for the high-risky industry in typical countries are then assessed. The set of rules and standards that govern risks of offshore operations in Chinese regulatory context are specifically presented. A key theoretical debate on regulating offshore drilling operations is which regulatory modes can better facilitate the robustness of risk regulation. The command-and-control regulation and self-regulation represent two primary regulatory modes for offshore risk regulation. The former is strongly dependent upon public enforcement, while the latter emphasizes internal continuous improvement of offshore petroleum industry. To develop robust offshore regulation in China, this paper suggests that some combination of the two modes will be necessary to deliver optimal regulatory outcomes.